2014
DOI: 10.1055/s-0034-1395987
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Hypercalcemia Secondary to Subcutaneous Fat Necrosis Successfully Treated with Pamidronate: A Case Series and Literature Review

Abstract: Subcutaneous fat necrosis (SCFN) is a noninfectious panniculitis that occurs in term infants who experience significant distress in the 1st weeks of life, including hypoxic ischemic encephalopathy (HIE). Since the introduction of therapeutic hypothermia for HIE, there have been a few published case reports of SCFN, following this modality of treatment. Although, most cases of SCFN resolve spontaneously, SCFN may be associated with hypercalcemia, which may sometimes reach dangerous levels. Approaches used for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Corticosteroids and bisphosphonates may be used for further management when adequate reduction in calcium levels is not obtained with the first-line intervention [ 3 ]. Samedi et al [ 19 ], in a case report, noted that the use of pamidronates (a bisphosphonate) had a faster onset of action than corticosteroids and thus advocated it as a possible first-line management of SFN with very severe hypercalcemia. Similarly Alos et al [ 20 ] in a case series involving four infants found that after initial trial of hydration and diuretics and there was not much reduction in iCa levels there was documented good outcome with the use of pamidronates.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids and bisphosphonates may be used for further management when adequate reduction in calcium levels is not obtained with the first-line intervention [ 3 ]. Samedi et al [ 19 ], in a case report, noted that the use of pamidronates (a bisphosphonate) had a faster onset of action than corticosteroids and thus advocated it as a possible first-line management of SFN with very severe hypercalcemia. Similarly Alos et al [ 20 ] in a case series involving four infants found that after initial trial of hydration and diuretics and there was not much reduction in iCa levels there was documented good outcome with the use of pamidronates.…”
Section: Discussionmentioning
confidence: 99%
“…Regular full skin observation is suggested in view of the potential complications during TH such as subcutaneous fat necrosis, a benign condition characterized by inflammation and necrosis of subcutaneous fat, and cold panniculitis which is an acute nodular, erythematous eruption. In the TOBY RCT 1% of infants had subcutaneous fat necrosis (204) which can be complicated by hypercalcaemia and require hyperhydration and diuretic treatment (205). Sclerema neonatorum is a diffuse hardening of the subcutaneous tissue during TH that usually self resolves.…”
Section: Skinmentioning
confidence: 99%